Analisis Peningkatkan Kemampuan Pemecahan Masalah Dan Kemandirian Belajar Dampak Flipped Classroom Berbantuan Video Pembelajaran - Marista Sari; Bambang Sri Anggoro; Iip Sugiharta (Nabla Dewantara, 2020)
A good education will create a good generation so that the lives of nations and countries will have a good effect. The purpose of this research is to analyze the influence of flipped classroom learning models assisted by Video Learning to improve problem solving skills and learning independence. The research method used is quantitative with quasy experimental design type. The sampling techniques in this study used randomized classroom techniques as experiment classes with flipped classroom learning models, control classes that used expository models. The data analysis technique used in this study is the Manova test with the conclusion that there is an influence on the use of flipped classroom learning models assisted by learning videos to improve solving skills. There is an influence on the use of flipped classroom learning models assisted by learning videos to improve learning independence. There is an influence on the use of flipped classroom learning models assisted by learning videos to improve mathematical problem solving skills and learning independence